2015
DOI: 10.1016/j.celrep.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

RNF168 Promotes Noncanonical K27 Ubiquitination to Signal DNA Damage

Abstract: Ubiquitination regulates numerous cellular processes by generating a versatile communication system based on eight structurally and functionally different chains linked through distinct residues. Except for K48 and K63, the biological relevance of different linkages is largely unclear. Here, we show that RNF168 ubiquitin ligase promotes noncanonical K27-linked ubiquitination both in vivo and in vitro. We demonstrate that residue K27 of ubiquitin (UbK27) is required for RNF168-dependent chromatin ubiquitination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 34 publications
2
138
0
Order By: Relevance
“…RNF8 or RNF168 deficient cells display impaired cellular responses to DNA damage, a defective G2/M checkpoint and increased radiosensitivity (Doil et al, 2009;Huen et al, 2007). In addition to K63 linked ubiquitination, RNF168 promotes noncanonical K27 linked ubiquitination in vivo and in vitro, and this specific ubiquitination is also required for the proper activation of the DNA damage response (Gatti et al, 2015). Additionally, the polycomb repressive complex 1, which contains Bmi1, Ring1, and Ring2, is required for H2A/H2AX ubiquitination (Bergink et al, 2006;Cao et al, 2005).…”
Section: Ubiquitinationmentioning
confidence: 99%
“…RNF8 or RNF168 deficient cells display impaired cellular responses to DNA damage, a defective G2/M checkpoint and increased radiosensitivity (Doil et al, 2009;Huen et al, 2007). In addition to K63 linked ubiquitination, RNF168 promotes noncanonical K27 linked ubiquitination in vivo and in vitro, and this specific ubiquitination is also required for the proper activation of the DNA damage response (Gatti et al, 2015). Additionally, the polycomb repressive complex 1, which contains Bmi1, Ring1, and Ring2, is required for H2A/H2AX ubiquitination (Bergink et al, 2006;Cao et al, 2005).…”
Section: Ubiquitinationmentioning
confidence: 99%
“…Recently, Penengo and colleagues have investigated the functional relevance of different types of ubiquitylation in the DDR (Gatti et al, 2015) and observed that RNF168 promotes K27-linked polyubiquitylation of histone 2A (H2A) proteins and that this linkage represents the major ubiquitin chain type on chromatin upon DNA damage, as shown by using selected reaction-monitoring mass spectrometry. Crucial DDR mediators such as 53BP1, Rap80, RNF168 and RNF169 recognize these K27-linked ubiquitin chains on histones H2A and H2A.X, and the inability of a cell to form K27 linkages prevents activation of the DDR because mediators can no longer be recruited (Gatti et al, 2015).…”
Section: K11 Linkages In Heterotypic Ubiquitin Conjugates -A Powerfulmentioning
confidence: 99%
“…The RAP80 complex specifically deubiquitinates the Lys 63 -ubiquitin chains through the actions of its associated Zn 2ϩ -dependent deubiquitinating enzyme, BRCC36. Unresolved questions remain as to whether deubiquitinating enzyme activity serves to terminate DNA damage association by removing the Lys 63 -ubiquitin recognition signal for RAP80 or, alternatively, in a ubiquitin-editing capacity, whereby it removes Lys 63 -ubiquitin, thus allowing accumulation of either monoubiquitin or other ubiquitin topologies that have been reported at DSBs (23). That loss of any member of the RAP80 complex eliminates observable BRCA1 focus formation at DSBs raises the question of whether the RAP80 complex accounts for BRCA1 function in HR.…”
Section: Connecting Brca Network Biochemistry To the Ddrmentioning
confidence: 99%